ARTIFICIAL INTELLIGENCE: A NEW PATHWAY IN SCREENING, DIAGNOSIS AND TREATMENT OF COLORECTAL CANCER - Yong, Elizabeth; Nee Teo, Yen; McKnoulty, Leanne; Gautam, Ajeevan; Chaulagain, Rajib; Hing Yong, Kun (Journal of Chitwan Medical College, 2024)
The increasing incidence of global colorectal cancer (CRC) cases is overwhelming the CRC healthcare industry. Artificial intelligence (AI) comes to light at this juncture and offers hope for early detection, diagnosis and treatment. In turn, the CRC-associated mortality rate will be reduced in more efficient and cost-effective ways. Nonetheless, despite the potential benefits of AI technology in the CRC healthcare industry, its applications are still in the early stages, and much work is required before its advantages are fully leveraged.